Pathohistological and immunohistochemical features of chronic viral hepatitis b progression - M. A. Shishkin (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
Aim. The paper contains the results of a comprehensive study of pathohistological and immunohistochemical liver biopsies of 50 patients with chronic hepatitis B in relation to clinical and biochemical parameters to improve the most significant microscopic criteria of chronic hepatitis B progression in liver trepanobioptates of the patients.